Hubungan Mobilisasi Dini Dengan Tingkat Nyeri Pada Pasien Post Sectio Caesarea di Ruang Carolus Borromeus 3 Kebidanan dan Kandungan Rumah Sakit Pantirapih Yogyakarta - Fajri, Anidya Ismi Yudistya; Agnes Mahayanti; Therese Maura Hardjanti (I Care Jurnal Keperawatan STIKes Panti Rapih, 2022)
ABSTRACT Background: Pain is a person's personal experience that is expressed differently in each individual and each individual has experience of pain on a certain scale, pain is also a stressor that can cause tension, this is an individual response where the body will respond biologically and behaviorally. Which causes physical and psychological responses, apart from that pain is also influenced by several factors, namely age, occupation, education and parity. Objective: Identify the Relationship between Early Mobilization and Pain Levels in Post-Caesarean Section Surgery Patients in the Carolus Borromeus 3 Obstetrics and Gynecology Room at Panti Rapih Hospital Yogyakarta. Methods: The study design used a quantitative analytic with cross sectional approach, the population was all post sectio Caesarea mothers who were treated in the Carolus Borromeus 3 obstetrics and gynecology room at Panti Rapih Hospital Yogyakarta. Samples were obtained by accidental sampling technique, namely patients who were met from 21 December 2020 to 21 January 2021 with a sample size of 36 respondents,instruments used a questionnaire and observation sheet. Results: The results showed that there was a relationship between mobilization and the level of pain (p value 0.027) where it was found that 88.89% of respondents had a good level of mobilization and 11.11% of respondents had a sufficient level of mobilization while 88.89% of respondents had a mild pain level. And 11.11% had moderate pain levels. Conclusion: There is a relationship between early mobilization and the level of pain in post sectio caesarean patients in the Carolus Borromeus 3 obstetrics and gynecology Panti Rapih Hospital Yogyakarta (p value 0,027), Suggestion: As an additional reference to the nursing profession in an effort to reduce pain in nursing care, it is not only maternity nursing but medical surgery nursing.